CD13 as a potential theranostic target for prostate-specific membrane antigen-negative prostate cancer and first-in-human study of [18F]AlF-CD13-L1 PET/CT imaging. - Tang, Wei; Zhou, Ming; Lu, Chenxi; Qi, Lin; Zhang, Ye; Tang, Yongxiang; Gao, Xiaomei; Hu, Shuo; Cai, Yi (European Journal of Nuclear Medicine & Molecular Imaging, 2025)
Purpose: Approximately 10% of prostate cancer (PCa) are prostate-specific membrane antigen (PSMA)-negative, leading to blind spots in PSMA-based diagnosis. This study aimed to identify a potential target for PSMA-negative PCa and preliminarily evaluate the feasibility of using radionuclide probe targeting the identified target for PCa diagnosis. Methods: Quantitative protein analysis was performed on eight PSMA-negative PCa and eleven controls to identify a potential molecular target, followed by validation with an expanded cohort using immunohistochemistry. Sixteen participants underwent [18F]AlF-CD13-L1 PET/CT scanning, with the PCa pathological tissues used as references to interpret the imaging results. Results: Quantitative protein analysis revealed CD13 as the most significantly upregulated membrane protein in PSMA-negative PCa. Expanded validation results indicated that CD13 positivity rates were 92.9% (13/14), 82.7% (105/127), 91.7% (11/12), and 70% (14/20) in PSMA-negative PCa, PSMA-positive PCa, ductal adenocarcinoma of the prostate (DAC), and intraductal carcinoma of the prostate (IDC-P), respectively. In PCa participants, the median [18F]AlF-CD13-L1 PET/CT maximum standardized uptake value (SUVmax) of tumors and tumor-to-muscle ratio were 4.3 (1.5–5.8) and 4.6 (1.7–6.1), respectively. The SUVmax value of the PCa lesions and the tumor-to-muscle ratio showed a positive correlation with the immunohistochemical score of CD13 of the PCa lesions (rspearman = 0.6249, p = 0.025; rspearman = 0.6714, p = 0.015, respectively), with CD13-positive tumors showing significant radiotracer accumulation. Conclusion: CD13 was a potential target for PSMA-negative PCa and also showed high positivity rates in PSMA-positive PCa, DAC, and IDC-P. [18F]AlF-CD13-L1 selectively accumulated in CD13-positive PCa, enabling visualization. (Trial registration: ChiCTR2300077817. Registered November 21, 2023).